2007
DOI: 10.1136/thx.2006.064428
|View full text |Cite
|
Sign up to set email alerts
|

Profiling serum biomarkers in patients with COPD: associations with clinical parameters

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is an inflammatory lung disease associated with significant systemic consequences. Recognition of the systemic manifestations has stimulated interest in identifying circulating biomarkers in these patients. A systematic analysis was undertaken of multiple protein analytes in the serum of well characterised patients with COPD and matched controls using novel protein microarray platform (PMP) technology. Methods: Forty-eight patients (65% men) with COPD (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
169
4
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(192 citation statements)
references
References 56 publications
15
169
4
4
Order By: Relevance
“…[5][6][7][8] Finally, peripheral blood biomarkers have been shown to correlate with mortality and other important clinical outcome measures ( Table 2 ). [9][10][11] Of note, although there is emerging research exploring other innovative peripheral blood-based biomarkers, such as changes in cell populations (fi brocytes, 12 T-cell subtypes, 13 monocytes), transcriptional changes (genes, microRNAs, noncoding RNA), autoantibodies, mark ers of oxidative stress, proteomics, and metabolomics, these areas are beyond the scope of this review. Throughout the rest of this perspective, we use the term "biomarker" to refer exclusively to a peripheral blood protein biomarker.…”
Section: Biomarker Approaches and Limitationsmentioning
confidence: 99%
See 3 more Smart Citations
“…[5][6][7][8] Finally, peripheral blood biomarkers have been shown to correlate with mortality and other important clinical outcome measures ( Table 2 ). [9][10][11] Of note, although there is emerging research exploring other innovative peripheral blood-based biomarkers, such as changes in cell populations (fi brocytes, 12 T-cell subtypes, 13 monocytes), transcriptional changes (genes, microRNAs, noncoding RNA), autoantibodies, mark ers of oxidative stress, proteomics, and metabolomics, these areas are beyond the scope of this review. Throughout the rest of this perspective, we use the term "biomarker" to refer exclusively to a peripheral blood protein biomarker.…”
Section: Biomarker Approaches and Limitationsmentioning
confidence: 99%
“…It is important to note that because of the cross-sectional nature of this study, the proteomic profi le was not shown to be related to mortality. 11 We also showed in the Evaluation of COPD Longitudinally to Identify Predictive Surrogate Endpoints (ECLIPSE) study that a combination of candidate biomarkers can improve the accuracy of predicting the risk of death in patients with COPD when added to clinical variables, such as age, FEV 1 , BODE index, and hospitalizations, known to predict mortality in COPD. 10 The addition of fi brinogen, CCL-18, SP-D, CRP, Clara cell protein-16, IL-6, IL-8, and TNF-a to clinical variables significantly improved the predictive model for mortality, with IL-6 having the greatest impact.…”
Section: Cc-chemokine Ligand-18 (Or Pulmonary and Activation-regulatementioning
confidence: 99%
See 2 more Smart Citations
“…In a small study of patients with mild to moderate COPD, serum pulmonary and activation-regulated chemokine/CC-chemokine ligand-18 (PARC/CCL-18) was significantly associated with reduced FEV1, increased risk of exacerbations, and an increased BODE index (Pinto-Plata et al 2007). There is also recent evidence that elevated levels of PARC/CCL-18 are associated with increased risk of cardiovascular hospitalizations or mortality in the lung health study (LHS) cohort and with total mortality in the ECLIPSE cohort (Sin et al 2011).…”
Section: C-reactive Proteinmentioning
confidence: 99%